Oral Presentation No. 019 Bi-directional cross talk between coagulation, fibrinolysis and inflammatory pathways in patients with ST-segment elevation myocardial infarction. (21st October 2022) - Kanji, Rahim; Gue, Ying X; Farag, Mohammed F; Mutch, Nicola J; Gorog, Diana A
Abstract: Background: Impaired endogenous fibrinolysis is a risk factor for recurrent cardiovascular events in patients with acute coronary syndrome (ACS). Ongoing inflammation is also an adverse prognostic risk factor. While inflammatory markers are elevated in patients presenting with ST-segment elevation myocardial infarction (STEMI), whether there is a direct relationship between markers of inflammation at presentation, and the effectiveness of endogenous fibrinolysis in this setting, is unclear. Our study aimed to assess the relationship between markers of inflammation, coagulation and fibrinolysis, in patients with STEMI. Material and methods: We conducted a prospective, observational study in consecutive patients presenting with STEMI. Blood was drawn on admission after dual antiplatelet therapy loading, but before administration of anticoagulants. The sample was immediately tested to assess endogenous fibrinolysis using the point-of-care Global Thrombosis Test. In addition, blood samples were tested for leucocyte and neutrophil count, neutrophil-to-leucocyte ratio (NLR), platelet-to-leucocyte ratio (PLR), fibrinogen, standard coagulation markers and high sensitivity C-reactive protein (hs-CRP). Results and conclusions: The cohort consisted of 129 patients (aged 66 ± 13 years, 78% male). Whole blood endogenous fibrinolysis time correlated with fibrinogen (r = 0.300, P = 0.001) and hs-CRP (r = 0.236, P = 0.011). Hs-CRP correlated with fibrinogen (r = 0.631, P < 0.001). There was no relationship between whole blood lysis time and leucocyte count, NLR, PLR, international normalised ratio or activated partial thromboplastin time. The effectiveness of endogenous fibrinolysis in whole blood is related to fibrinogen and hs-CRP levels. Our findings strengthen the evidence for bi-directional cross talk between coagulation, fibrinolysis and inflammatory pathways, providing mechanistic insights that could help guide pharmacological strategies to treat hypofibrinolysis.